Usefulness of the Bolus-Tracking Baseline Scan for the Diagnosis of Hepatic Steatosis in Abdominal Computed Tomography: A Feasibility Study. (27th April 2013) - Gossner, J.; Schäfer, S.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is a common pathology in western societies. Unenhanced computed tomography (CT) of the liver is a valuable tool in determining the presence of steatosis hepatis, but in most departments standard CT protocols of abdomen often do not include unenhanced scans anymore. In a small series of 22 patients the liver density was measured in the acquired low-dose baseline scan for bolus tracking and was compared to the measurement in a regular unenhanced CT scan of the upper abdomen. The mean difference between the unenhanced CT scan and the low-dose baseline scan was 3.4 HU (range 0.2–8.6 HU); the difference between these two scans was 5 HU or smaller in 82% of the patients. There was a significant difference between the two used CT scanners; this has to be kept in mind before implementing this approach into daily practice. All but one patient with fatty liver disease on unenhanced CT were diagnosed using the baseline scan. The baseline scan for bolus tracking may be useful for the diagnosis or in the followup of fatty liver disease.